Work-related musculoskeletal problems and the associated risk factors among rubber tappers: A case study at a village in Northern Peninsular Malaysia - Ezrin Hani, Sukadarin; Tong, Sudaratt Pet; Balqis Syahirah, Jamaludin; Junaidah, Zakaria; Nur Syazwani, Mohd Nawi (Human Factors and Ergonomics Society Malaysia (HFEM), 2019)
Rubber tapping involves repetitive and high paced work, static muscle loading, non-neutral body postures, forceful physical exertion, and many other potential risk factors for development of work-related musculoskeletal problems (WRMP). In this research, a cross-sectional study was carried out to identify the prevalence of WRMP among rubber tappers, to determine the psychosocial factors that contribute to WRMP, and to explore the relationship between psychosocial factors and physical factors among rubber tappers. Data collection was done using three instruments, namely Nordic Musculoskeletal Questionnaire (NMQ), Job Content Questionnaire (JCQ) and Rapid Upper Limb Assessment Tools (RULA). In total, 70 rubber tappers participated in this study. Results obtained in study revealed that majority of the rubber tappers suffering from lower back pain whereas in terms of psychosocial factors they have low social support and high job and physical demand. WRMP among rubber tappers are cannot be doubtable, however the risk can be reduced if the management of occupational safety and health risk is managed properly.